2004
DOI: 10.1097/00005537-200401000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Results after Interval Therapy with Intratympanic Gentamicin for Menière's Disease

Abstract: Our results with this group of patients after interval-treatment or single-shot application of intratympanic gentamicin demonstrate the effectiveness of this treatment modality with very low side effects, and, although our experience is still limited, it allows for expanding the indication on early cases of Menière's disease before permanent hearing loss occurs. Even cases of bilateral Menière's disease can be treated successfully using this method. Cochleotoxic side effects can be prevented by treatment inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 9 publications
3
52
0
Order By: Relevance
“…Local anaesthetics and aminoglycosides were applied decades ago to treat inner ear disorders (1,2,3). The present, most widely used form of intratympanic therapy is the injection of gentamicin into the middle ear in patients with Menière's disease (3,4,5,6,7,8). Gentamicin is toxic to the sensory cells of the balance system and thereby suppresses the vertigo in these patients by partially ablating their vestibular system.…”
Section: Introductionmentioning
confidence: 99%
“…Local anaesthetics and aminoglycosides were applied decades ago to treat inner ear disorders (1,2,3). The present, most widely used form of intratympanic therapy is the injection of gentamicin into the middle ear in patients with Menière's disease (3,4,5,6,7,8). Gentamicin is toxic to the sensory cells of the balance system and thereby suppresses the vertigo in these patients by partially ablating their vestibular system.…”
Section: Introductionmentioning
confidence: 99%
“…Most authors believe there is no relationship between the caloric response after intratympanic gentamicin treatment and the degree of vertigo control. 8,17,18 In 2004, Cohen-Kerem et al 19 published a metaanalysis of intratympanic gentamicin treatment for Ménière's disease. Unfortunately, the evaluated data were not completely comparable, since the various studies had differing administration techniques and improvement criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study which used up to three interval doses of just 12 mg gentamicin within 15 days showed no deleterious effect on hearing. 19 A retrospective study of patients with unilateral Ménière's disease who received several intratympanic dexamethasone injections demonstrated acceptable vertigo control in 91 per cent of patients, although dosages and hearing effects were not documented. 20 Surgical treatment of Ménière's disease via vestibular neurectomy is associated with a 40 per cent risk of hearing loss despite a 94 per cent rate of vertigo control; 21 however, saccus decompression leads to a vertigo control rate of 80 per cent, with less risk to hearing.…”
Section: Discussionmentioning
confidence: 99%